2014
DOI: 10.1097/pgp.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Cell

Abstract: Summary In 1976, a series of 12 cases describing a lesion that had previously not been well characterized was reported as “trophoblastic pseudotumor of the uterus.” Up until that time rare reports of the lesion had classified it most often as an unusual type of sarcoma associated with pregnancy. All patients in that series were alive and well except for one who died from complications of a uterine perforation occurring at the time of a diagnostic curettage. Thus, it appeared to be a benign neoplasm but subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…The above process is subject to strict temporal and spatial regulation in normal placentation (17). It is considered that PSTT is caused by hyperplasia of intermediate trophoblast, while hydatidiform mole and choriocarcinoma are results of abnormal or malignant proliferation of syncytiotrophoblast and cytotrophoblast (18, 19). Others propose that PSTT forms during the process of placenta detaching from the uterus, and the small nodules of the placental tissue remaining in the myometrium, and being reabsorbed over time.…”
Section: Mechanismmentioning
confidence: 99%
“…The above process is subject to strict temporal and spatial regulation in normal placentation (17). It is considered that PSTT is caused by hyperplasia of intermediate trophoblast, while hydatidiform mole and choriocarcinoma are results of abnormal or malignant proliferation of syncytiotrophoblast and cytotrophoblast (18, 19). Others propose that PSTT forms during the process of placenta detaching from the uterus, and the small nodules of the placental tissue remaining in the myometrium, and being reabsorbed over time.…”
Section: Mechanismmentioning
confidence: 99%
“…In fact, approximately 75% of patients with ovarian cancer have advanced stage disease by the time the symptoms become apparent. 2 Involving both pelvic and abdominal peritoneum, these tumors commonly spread along peritoneal surfaces including the mesentery, diaphragm, omentum and surfaces of solid organs such as liver and spleen. It has been reported that less than 25% of patients with stage III/IV HGSCs will be cured by current therapies and the median survival for stage IV is 23 months.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that less than 25% of patients with stage III/IV HGSCs will be cured by current therapies and the median survival for stage IV is 23 months. 2 Thus, there is a great need for novel approaches to treat this tumor.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In early placental development, trophoblasts are considered as “pseudo-tumor cells” and share certain similar mechanisms with malignant cells in tumorigenesis and metastasis. [6,7] It is worth noting that genetic factors are believed to be involved in the development of severe preeclampsia (SPE). [8,9]…”
Section: Introductionmentioning
confidence: 99%